2020
DOI: 10.1080/15438627.2020.1784176
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceptions of mental fatigue during a season in professional under-23 English Premier League soccer players

Abstract: The present study assessed changes in academy soccer players' perception of mental fatigue (MF) across a competitive season, investigating the relationship between MF and other subjective measures of wellness. Ten players completed a modified Brief Assessment of Mood (BAM+) questionnaire that included the question: 'How mentally fatigued do you feel'? on match-day (MD) and one (MD+1), two (MD+2) and three (MD+3) days post-match (35 matches). Players reported their MF, along with other subjective measures (slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 28 publications
6
34
0
Order By: Relevance
“…Recent investigations with well-trained netballers and soccer players show that the subjective rating of MF remains higher than pre-training/competition during a netball training camp and after a soccer match (Abbott et al, 2020;Russell et al, 2021;Thompson et al, 2020). This might reinforce the consensus made by the expert panel that insufficient recovery, the physical and cognitive demands of the task together with the unpredictability of the environment, may be related to the development of MF.…”
Section: The Definition Of Mental Fatiguementioning
confidence: 79%
“…Recent investigations with well-trained netballers and soccer players show that the subjective rating of MF remains higher than pre-training/competition during a netball training camp and after a soccer match (Abbott et al, 2020;Russell et al, 2021;Thompson et al, 2020). This might reinforce the consensus made by the expert panel that insufficient recovery, the physical and cognitive demands of the task together with the unpredictability of the environment, may be related to the development of MF.…”
Section: The Definition Of Mental Fatiguementioning
confidence: 79%
“…Regarding the between match recovery for mental fatigue, previous studies suggested that mental fatigue remains elevated for a period of time, although the cognitively fatiguing task had finished [9,10]. For example, the fact that the increase in the mental fatigue 24 h after a soccer match had finished was described in two different studies [22,24]. Although this is not clear in padel yet, and other previous papers have not reported negative effects of mental fatigue [11,12], the information provided in previous studies indicate that a decrease in padel performance may occur in presence of mental fatigue [13,14].…”
Section: Mental Fatiguementioning
confidence: 99%
“…Soccer is primarily a low-intensity endurance activity interspersed with repeated short bouts of high-intensity activity [ 1 ]. However, soccer is also cognitively demanding and fatiguing [ 5 , 6 ]. It has been stated that soccer is one of the highest cognitive demand sports due to its performance being influenced by high levels of attention and frequent decision making [ 7 ].…”
Section: Introductionmentioning
confidence: 99%